Haematological analysis on sub acute oral toxicity study of water extract from leaves of hibiscus rosa sinensis l. in Balb/C mice - Norazharr, Siti Hajar (2017)
The leaves of Hibiscus rosa-sinensis are widely used in some country such as Japan, India and Haiti as herbal medicine to promote wound healing, hair growth and for the treatment of fever. However, the consumption of Hrosa-sinensis leaves as herbal medicine have raised concerns with regard to its dosage range that can be safely utilised among consumers. Although, there is study that has been conducted in assessing Hirosa-sinensis leaves of methanolic extract in Swiss Albino mice, toxicity study on the water extract of H.rosa leaves in BALB/c mice is still absent. The aim of this study is to look at the effect of repetitive administration of water extract Hrosa-sinensis leaves on haematological parameter in BALB/c mice. The leaves of Hirosa-sinensis were collected around UiTM Puncak Alam was prepared by aqueous extraction. In this sub-acute toxicity study, twenty-four BALB/c mice were used. The mice were randomly divided into four groups (n=6). Each group were given either distilled water (control), 50,300 or 2000 mg/kg doses of extract respectively for 28-days via oral gavage. Food intake and body weight were recorded at weekly interval throughout the experimental duration. At the end of this study, the mice were sacrificed by using pentobarbital (0.2ml/mice) intraperitonially. Then blood was collected by cardiac puncture and haematological analysis (RBC and WBC count) was conducted. In the sub-acute toxicity study, administration of 50,300 and 2000mg/kg doses of extract to mice for 28-days did not show any significant toxicity effect on haematological parameters nor behavioural effect in the BALB/c mice. Body weight, food consumption and haematological parameter analysis also showed no significant changes in this study.